Genetic diversity and seed supply variables affecting the regeneration of sandalwood in Gunung Sewu: Implications for sustainable forestry - Utami Sulistyaning H.; Ratnaningrum Yeni W.N.; Prehaten Daryono (BIO Web of Conferences)
Data series from 2012 to 2022 has documented the genetic and reproductive aspects of 14 sandalwood landraces in Gunung Sewu Geopark, Java Island. Several landraces are of importance for their presence of rare alleles, the high genetic diversity and mating ability, and the abundant seed sets; therefore, they are projected to be the seed sources. Despite these superior traits, crucial problems exist for the progeny qualities. This study aimed to determine the effects of seed supply variables, with regard to floral traits and parental genetic diversity, on the progeny qualities of selected sandalwood seed sources in Gunung Sewu during the 2022 to 2023 flowering period. Floral traits were represented by the abundance of flowers and flowering trees. The isozyme-based assessment estimated the parental genetic diversity. Results revealed that more flowers and seeds maintained more seed banks and developed more seedlings. The parental heterozygosity was positively significant to the seed sets but was insignificant to the seed bank and seedling abundances. This implied that floral traits and parental genetic diversity might determine seed quality and quantity, but further development of these seeds will need more intervention from more favorable seed beds and environmental features.